Study on Roof Tile’s Colors in Malaysia for Development of new Anti-warming Roof Tiles with Higher Solar Reflectance Index (SRI) - Alyacouby, Ahmad (2011)
This paper presents the preliminary findings of on going study intended to develop a cool house by introducing roofing materials with higher Solar Reflectance Index (SRI). SRI is a composed measure that accounts for surface’s solar reflectance and emittance. It is measured on a unitless scale from 0 to 1. Residential buildings in Malaysia are experiencing overheating of roof space due to inappropriate selection of roofing systems and materials. This badly affects the indoor thermal comfort of low rise buildings where roof represents 70% of heat gain. Emissions from building sectors are about 8.6Gt of CO2 per year. The thermal performance of a building is affected by the solar absorbance of roof. During a clear sky conditions up to 1kW/m2 of radiation can be incidental on a roof surface and between 20% and 90% of this radiation is typically absorbed. This study emphasizes on observation and documentation of main parameters which influence SRI of roof tiles i.e. (1) Roof color, (2) material composition, and (3) the degree of roof slope. The research methodology consists of (1) construction of one unit experimental house to study the effects of SRI of roof on indoor thermal comfort, and (2) semi-structured questionnaire survey conducted to determine the roof colors on existing buildings in Malaysia. Home buyer’s roof color preference was also determined. The research outcomes will have important implication for application of cool roofs and sustainable development in Malaysia.